2022
DOI: 10.1002/acm2.13850
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis of the Unity 1.5 T MR‐Linac adapt‐to‐position workflow

Abstract: Background and Purpose: Newer technologies allow for daily treatment adaptation, providing the ability to account for setup variations and organ motion but comes at the cost of increasing the treatment workflow complexity. One such technology is the adapt-to-position (ATP) workflow on the Unity MR-Linac. Prospective risk assessment of a new workflow allows clinics to catch errors before they occur, especially for processes that include novel and unfamiliar steps. Methods: As part of a quality management progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Despite the valuable insights offered by these publications, there remains an absence of a universally accepted standard for identifying the threshold at which an RPN score requires attention. In contrast to prior studies that solely relied on either RPN or a risk matrix to assess the risk levels, our novel approach of incorporating a risk matrix alongside RPN considerations demonstrated that RPNs significantly lower than the thresholds proposed in the literature may still indicate a high level of risk and require specific attention 21–23 . Conversely, certain steps with low‐risk levels might yield high RPN values due to their high occurrence rate.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Despite the valuable insights offered by these publications, there remains an absence of a universally accepted standard for identifying the threshold at which an RPN score requires attention. In contrast to prior studies that solely relied on either RPN or a risk matrix to assess the risk levels, our novel approach of incorporating a risk matrix alongside RPN considerations demonstrated that RPNs significantly lower than the thresholds proposed in the literature may still indicate a high level of risk and require specific attention 21–23 . Conversely, certain steps with low‐risk levels might yield high RPN values due to their high occurrence rate.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast to prior studies that solely relied on either RPN or a risk matrix to assess the risk levels, our novel approach of incorporating a risk matrix alongside RPN considerations demonstrated that RPNs significantly lower than the thresholds proposed in the literature may still indicate a high level of risk and require specific attention. [21][22][23] Conversely, certain steps with low-risk levels might yield high RPN values due to their high occurrence rate. The analysis showed that human failures, such as inexperience, inattention, and a lack of thorough checks, are identified as the primary potential causes of these high-risk failure modes.…”
Section: Discussionmentioning
confidence: 99%